TIME SERIES EVIDENCE ON EDUCATION AND ECONOMIC GROWTH IN INDONESIA - Rahmatina A. Kasri (Universitas Islam Indonesia, 2011)
This paper analyzes the main sources of economic growth in Indonesia with emphasizes on education role in fostering the growth during the New Order Government. To arrive at conclusive results, it employs rigorous econometric techniques and Error Correction Models that consider structural adjustments in the economy. The study finds that physical capital and secondary education, particularly through the Universal Secondary Education Program, give the highest contribution to economic growth. It is also suggested that the negative effect of primary education on the long-run growth is mainly due to over-supply and excess-demand for the graduates following the structural changes in the economy. Keywords: Education, human capital, economic growth, error correction model JEL classification numbers: I25, O15, O43, O53, C22